2021
DOI: 10.1007/s10198-021-01343-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of influenza and pneumococcal vaccination in the elderly on health service utilisation and costs: a claims data-based cohort study

Abstract: Background To date, cost-effectiveness of influenza and pneumococcal vaccinations was assumed in several health economic modelling studies, but confirmation by real-world data is sparse. The aim of this study is to assess the effects on health care utilisation and costs in the elderly using real-world data on both, outpatient and inpatient care. Methods Retrospective community-based cohort study with 138,877 individuals aged ≥ 60 years, insured in a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(59 reference statements)
1
1
0
1
Order By: Relevance
“…Total mean costs were statistically significant higher for unvaccinated patients (EUR 12,002.56) than those vaccinated (EUR 10,650.66). This result coincides with Storch et al (2021), who found cost-saving effects for influenza vaccination in hospitalized cases [ 14 ]. In addition, ICU admission was statistically significant higher in the unvaccinated than in vaccinated patients.…”
Section: Discussionsupporting
confidence: 92%
“…Total mean costs were statistically significant higher for unvaccinated patients (EUR 12,002.56) than those vaccinated (EUR 10,650.66). This result coincides with Storch et al (2021), who found cost-saving effects for influenza vaccination in hospitalized cases [ 14 ]. In addition, ICU admission was statistically significant higher in the unvaccinated than in vaccinated patients.…”
Section: Discussionsupporting
confidence: 92%
“…Datengrundlage bildeten die Abrechnungsdaten der AOK Plus zu Thüringer Versicherten ≥ 60 Jahre aus dem vom Bundesministerium für Bildung und Forschung geförderten Verbundprojekt „Impfen60+ – Impfbereitschaft 60+ fördern“ (Förderkennzeichen: 03ZZ0819B; [ 15 ]). Diese Abrechnungsdaten dienten in der Primärstudie der gesundheitsökonomischen Evaluation der Influenza- und Pneumokokkenimpfungen [ 16 ] sowie der Analyse der Impfeffekte hinsichtlich der Krankheitslast [ 17 ] und unterlagen daher definierten Einschlusskriterien (siehe Onlinematerial).…”
Section: Methodenunclassified
“…Before the latest expansion of the German NIP in 2016 to include more coverage for elderly and at-risk individuals, two records estimated low overall VCRs with PCV13 in immunocompromised adults (4.4%) 94 and elderly people (3.2%). 100 However, after the change in NIP, more recent studies estimated a higher coverage rate for both sequential vaccination (9.9% who received PCV13+PPV23) as well as for PPV23 vaccination (35.1%) in the at-risk population. 76 Similarly higher VCRs were estimated in older populations after the German change in NIP (PPV23: 39%, 76 50% [ 74 ; PCV13: 38%; 74 overall: 30.3% 111 ].…”
Section: Vaccine Coverage Ratesmentioning
confidence: 99%